Papers - Foreign Production - Russian Oil Fields in 1928 and 1929 (With Discussion) - B. B. Zavoico (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1930)
Considerable progress has been made during the past year throughout the Russian petroleum industry. Perhaps the most remarkable achievement is the execution of the programs set out by the Central Planning Bureau of the Department of Commerce. These programs have been increased twice during the past operating year, necessitating drilling the richest reserves, instead of developing gradually as originally planned. The fulfillment of the set-out programs during the past few years makes therefore the present five-year plan of considerable importance to the international oil statisticians in approximating actual supply conditions up till 1933. The production of all Russian fields increased by 14,200,000 bbl. as compared with the 1927-1928 operating year, while the next year's program anticipates a further increase of 15,700,000 barrels. It appears therefore that production for 1932-33 will total 187,000,000 bbl., or approximately double that of the operating year just closed. It is also evident that the old fields are counted upon to produce only about 67 per cent. of the total, the new fields, not yet discovered, to furnish the balance of 33 per cent. The Soviet oil leaders therefore are hoping to have new fields discovered and developed by 1932-33. However, as in the past wildcatting